2017
DOI: 10.18326/rgt.v10i1.48-61
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Based Learning to Improve Students’ Grammar Competence

Abstract: ENGLISH ABSTRACT Grammar becomes one of the subjects studied in all Indonesian English Departments. It is because grammar has the important role in all English skills. Grammar makes those four English skills meaningful. Somebody can be said as a master of English when he or she also masters grammar. Unfortunately, learning grammar is not as easy as what we think. It needs the effective method that can make the learners motivated and active in learning as well as in applying the grammar in the real life. Proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…This reinforces the idea that students in this condition will easily and effectively speak in English so that their increased abilities can be categorized as significant improvements (Leong & Ahmadi, 2017). Especially in grammar assessment, this is true if being good at grammar during the speaking skill process is quite burdensome for students because learning grammar directly and learning grammar is very different indirectly (Zuhriyah, 2017). Therefore, the assessment of this aspect does not show a significant lift.…”
Section: Resultssupporting
confidence: 59%
“…This reinforces the idea that students in this condition will easily and effectively speak in English so that their increased abilities can be categorized as significant improvements (Leong & Ahmadi, 2017). Especially in grammar assessment, this is true if being good at grammar during the speaking skill process is quite burdensome for students because learning grammar directly and learning grammar is very different indirectly (Zuhriyah, 2017). Therefore, the assessment of this aspect does not show a significant lift.…”
Section: Resultssupporting
confidence: 59%
“…PBL emphasizes the integration of real-world problem-solving, critical thinking, and self-regulated active learning [ 29 ] via group discussion and peer collaboration [ 21 ]. In a PBL classroom, students are encouraged to decide on the problem and collectively generate objectives for their self-directed learning, while the teacher serves as a facilitator, rather than a content provider, to engage students to explore the content material [ 30 , 31 , 32 , 33 ]. Ali [ 19 ] suggested that in settings where PBL approach is used, students must take responsibility for their own learning, and teachers should act as facilitators or guides to encourage students to construct and seek meaning and solutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Speaking is the way for people to express something and for communicating to other people orally (Nurdin, 2021). Talking is a way of interacting with others in everyday life between interaction and communication (Zuhriyah, 2017). The use of English in Indonesia in daily activities is limited.…”
Section: Introductionmentioning
confidence: 99%